Water footprint of melon production under different nutrient and plant growth regulator management - Fadil Rohman; Leli Kurniasari; Maria Azizah; Refa Firgiyanto; M Zayin Sukri; Hanif Fatur Rohman; Didik Pudji Restanto; Etik Wukir Tini (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Applying environmentally friendly technology in melon cultivation aims to create sustainable agriculture. Nutrient and plant growth regulators management are simple to apply and have a relatively rapid effect on melon fruit production. Water footprint assessment in melon cultivation is crucial for ensuring sustainable agricultural practices and efficient water use. This study aimed to evaluate the electroconductivity of nutrient solutions and GA3 concentration in increasing fruit production and water footprint efficiency. This research was conducted from June to September 2022 at Tefa SGH Polije. This research used a completely randomized design with treatments that consisted of nine combinations of nutrient solution electrical conductivities (2.8, 3.2, and 3.6 mS cm-1) and GA3 concentrations (0, 60, and 120 mg L-1). Observation variables were fruit diameter, edible part thickness, fruit sweetness level, fruit weight, and water footprint. Data were analyzed using ANOVA and DMRT. Applying 2.8 mS cm-1 nutrient solution (NS) + 60 mg L-1 GA3 was the best treatment according to fruit diameter, edible part thickness, and fruit sweetness level. Although statistically, it had no significant effect, 2.8 mS cm-1 NS + 60 mg L-1 GA3 increased fruit weight by 18.75% and water footprint efficiency by 15.48% compared to control. Keywords: blue water footprint; evapotranspiration; gibberellins; nutrient solution